Molecular and Functional Characterization of Inhibitor of Apoptosis Proteins (IAP, BIRP) in Echinococcus granulosus - Zhan, Jiafei; Song, Hongyu; Wang, Ning; Guo, Cheng; Shen, Nengxing; Hua, Ruiqi; Shi, Yuan; Angel, Christiana; Gu, Xiaobin; Xie, Yue; Lai, Weimin; Peng, Xuerong; et al. (Frontiers in Microbiology, 2020)
The larval stage of Echinococcus granulosus sensu lato, resulting in cystic echinococcosis, a parasitic zoonosis, causes huge economic losses to the livestock industry and poses a threat to public health. Inhibitor of apoptosis proteins (IAPs) is a class of endogenous anti-apoptotic family, which plays a significant functional role in the regulation of organism’s development. Herein, to explore potential functions of IAPs in E. granulosus, two members of IAPs from E. granulosus (Eg-IAP and Eg-BIRP) were cloned, expressed, and molecularly characterized. Eg-IAP and Eg-BIRP encoded putative 331 and 168 residue proteins, respectively. Bioinformatic analysis showed that both proteins contained a type II BIR domain-the essential functional domain of IAPs. Fluorescence immunohistochemistry revealed that both proteins were ubiquitously localized in all life-cycle stages of E. granulosus. Our fluorescent quantitative PCR (RT-qPCR) results revealed relatively higher transcription levels of two Eg-IAPs in protoscoleces (PSCs) compared to the 18-day strobilated worms. We further used different concentrations of LCL161, a Smac-mimetic pan-IAPs inhibitor, to induce the apoptosis in PSCs in vitro, and revealed that the survival rate of PSCs and transcription levels of both genes were negatively correlated with the concentration of LCL161. While the results of light microscopy, transmission electron microscopy (TEM), and terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) assay also showed a higher apoptotic rate in PSCs with the increasing concentrations of LCL161. Taken together, our findings provide the reasonable evidence that both Eg-IAP and Eg-BIRP have potential implication in critical anti-apoptotic roles during the development of E. granulosus.